Survive in the mountains - Bowman, Chris, 1990- (Minneapolis, MN : Bellwether Media, Inc., 2017)
"Amazing photography accompanies engaging information about how to survive in the mountains. The combination of high-interest subject matter and light text is intended for students in grades 3 through 7"--
Plane crash -- Survive in the mountains -- Finding shelter -- Drinking water -- Eating food -- Avoiding animals -- Making fire and signals.
Includes bibliographical references and index.
Keywords: Wilderness survival -- Juvenile literature